(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Agriculture plays a vital role as the backbone of a nation’s economy. Rural sectors of India completely depend upon agriculture as their basic livelihood. Here Women’s agricultural labour force plays the most important contribution to the farming of the nation. Women agricultural labourers are socially and financially the poorest section of society. Unemployment, illiteracy, under nutrition, dual responsibility, shortage of wage, lack of access to resources, indecisive behaviour, and lack of efficiency in handling technology are major drawbacks of women agricultural labourers which create major hindrances in their working conditions In most of the developing societies, it is common to find a large number of poor people who are living out with a subsistence level of income could not able to come out of the grip of poverty. A multitude of factors– economic and non–economic are responsible for the problem of poverty. Any discussion on the problem of poverty in the Indian context is incomplete without references to landless agricultural workers, who are facing several problems on many fronts, are inevitably more vulnerable to the malice of unemployment, inequality and poverty. Faced with the seasonal nature of employment along with their poor resource capacity, they are forced to work very hard to make a decent life. In most cases, a typical Indian agricultural labour’s households contain more than one earning member and more dependent members. The need for women members of the Indian agricultural labourer’s family to go in work is forced because of inadequate employment opportunities and not that much.